Home energy use, lifestyle, and behaviour: a community energy saving programme (CESP) survey in Aspley, Nottingham - Eihab Abdelghaffar Elsharkawy, Heba (2013)
With increasing concern over national green house gas (GHG) emissions, combined with the widespread economic impact of global commodities such as coal, natural gas and oil and their effect on energy prices, improving household energy efficiency can be seen as a key vehicle against which both energy emissions can be reduced and domestic GHG emissions curtailed. It is argued that factors that form the basis of choices, habits and values of individuals dictate an individual's decision to either adopt environmentally sustainable behaviour or not. This research reflects on how this specific area of energy policy is being enacted through policy and regulation, notably through one of the Community Energy Saving Programme (CESP) schemes, rolled out by the UK government in 2009. Although Government can play a pivotal role helping people foster more sustainable behaviour, it must do so in a manner that engages individuals and the public at large. As such, the aim is to adopt a more long term outlook towards encouraging sustainable energy use. The research reflects therefore on the results of a two-phase survey questionnaire administered to the residents of a CESP scheme in Aspley, Nottingham. The questionnaire sought to identify how tenants of energy-inefficient homes tend to behave with respect to domestic energy consumption and how their dwellings performed. This was augmented by quantitative data comprising utility bill figures gathered from the homes under investigation. This study adopts a mixed method strategy where the researcher combines both quantitative and qualitative data in order to provide comprehensive analysis of the research problem. In this research, 'before-and-after design' survey design is set up to explore the associations between variables under study. The field work survey was performed in one of the pilot CESP schemes currently under delivery in the Aspley area of Nottingham. Designed and executed in two survey phases, the first phase sought to understand residents' attitudes and behaviour and explore how this related to home energy use and performance prior to extensive energy-related upgrades to their dwellings. The second survey phase sought to examine changes - if any - in users' energy consumption behaviour and dwelling performance after their homes were upgraded to higher energy efficiency standards. This second phase also explored the possible reasons for any behavioural change depicted; whether it was due to policy uptake, information provided or means of communicating energy saving advice. The Aspley area in Nottingham is identified as one of the most deprived areas in Nottingham, besides the number of inefficient solid wall houses that are 'hard to heat'. Thus, assessing the effectiveness of policy interventions requires a clear understanding of consumer behaviour and motivations across all income groups so that the most appropriate approaches are developed. As such, it is possible that government aspirations to reduce energy consumption will go unheeded if they are inconsistent with the social and physical context of real life. Financial costs, past behaviour, social values and physical infrastructure are considered some of the most difficult barriers to changing energy behaviours. Policies need not only inform people about technological improvements that can be installed in their homes, but should also strongly encourage and incentivise them to use them efficiently. The users' energy consumption behaviour and the policy interventions will make the difference between promising policy, and policy which in fact delivers on its aims for energy efficiency and sustainability.